2019
DOI: 10.1039/c9tc01509d
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite white light-emitting diodes based on a molecular blend perovskite emissive layer

Abstract: Perovskite white light-emitting diodes with only a single emissive layer were realized with CIE chromaticity coordinates of (0.3, 0.49).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 31 publications
1
45
1
1
Order By: Relevance
“…17 MHPs are appealing materials not only in photovoltaics but also in LEDs, photodetectors, lasers and other optoelectronic applications, where a signicant progress had been also reported. [18][19][20][21][22][23][24] Researchers have shown that a synergetic effect can be realized by combining the advantages of these two classes of materials: perovskites and nanocrystals. 25 Extensive research has therefore concentrated on the synthesis, characterization and application of MHP NCs and particularly lead halide perovskite NCs, which may substitute traditional metal chalcogenide NCs in some applications.…”
Section: Introductionmentioning
confidence: 99%
“…17 MHPs are appealing materials not only in photovoltaics but also in LEDs, photodetectors, lasers and other optoelectronic applications, where a signicant progress had been also reported. [18][19][20][21][22][23][24] Researchers have shown that a synergetic effect can be realized by combining the advantages of these two classes of materials: perovskites and nanocrystals. 25 Extensive research has therefore concentrated on the synthesis, characterization and application of MHP NCs and particularly lead halide perovskite NCs, which may substitute traditional metal chalcogenide NCs in some applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, efficient white perovskite LEDs remain a significant challenge. Mixing single-color perovskite material with organic compound 7,8 and stacking perovskite layers with various colors 9 have been used to achieve white lead-halide perovskite LEDs, but the peak EQE is only 0.22% 9 . Alternatively, various metal halides possessing broadband white-light emission, such as two-dimensional lead halide perovskite [10][11][12] , lead-free halide double perovskite 13 , and cesium copper halides 14 , have been developed to be emitters in white LEDs.…”
mentioning
confidence: 99%
“…For instance, green-emitting Br 3 -based LEDs with EQEs of up to 17.5% and 20.3% have been demonstrated by Zhang et al [171] and Lin et al [172], respectively. While these EQEs are far from those offered by InGaN-based LEDs, easy solution-processability makes these materials attractive for applications in solid-state lighting and nextgeneration display technologies [164,[173][174][175][176][177]. In addition, various perovskite-based photodetectors with high responsivities [178][179][180], flexibility [181][182][183][184], and fast response speeds [150,178,[185][186][187] have also been demonstrated widely [188].…”
Section: State-of-the-art Devicesmentioning
confidence: 99%